Enhancing the implantation of mechanical circulatory support devices using computational simulations - Lopez-Santana, Gabriela; De Rosis, Alessandro; Grant, Stuart; Venkateswaran, Rajamiyer; Keshmiri, Amir (Frontiers in Bioengineering and Biotechnology, 2024)
Patients with end-stage heart failure (HF) may need mechanical circulatory support such as a left ventricular assist device (LVAD). However, there are a range of complications associated with LVADs including aortic regurgitation (AR) and thrombus formation. This study assesses whether the risk of developing aortic conditions can be minimised by optimising LVAD implantation technique. In this work, we evaluate the aortic flow patterns produced under different geometrical parameters for the anastomosis of the outflow graft (OG) to the aorta using computational fluid dynamics (CFD). A three-dimensional aortic model is created and the HeartMate III OG positioning is simulated by modifying (i) the distance from the anatomic ventriculo-arterial junction to the OG, (ii) the cardinal position around the aorta, and (iii) the angle between the aorta and the OG. The continuous LVAD flow and the remnant native cardiac cycle are used as inlet boundaries and the three-element Windkessel model is applied at the pressure outlets. The analysis quantifies the impact of OG positioning on different haemodynamic parameters, including velocity, wall shear stress, pressure, vorticity and turbulent kinetic energy. We find that WSS on the aortic root is around two times lower when the OG is attached to the coronal side of the aorta using an angle of 45±10° at a distance of 55 mm. The results show that the OG placement may significantly influence the haemodynamic patterns, demonstrating the potential application of CFD for optimising OG positioning to minimise the risk of cardiovascular complications after LVAD implantation.